Tradução e adaptação transcultural da Mishel Uncertainty In Illness Scale – Parents/Child Form - Brasileiro, Renata Sá Ferreira (2016)
The study aimed the translation and cultural adaptation of Mishel Uncertainty in Illness scale - parents / child form to portuguese in the Brazilian context. Study of methodological type, used as methodology the translation and adaptation of procedures suggested by Beaton (2007) that includes initial translation, translation synthesis, back-translation, review by a committee of judges and pre-test with the target audience. Participants were five judges, during the review stage by a committee of judges, and 35 mothers of children with neurological affections, during the phase of the translated version pre-test. During the pre-test was applied the translated version of the scale, produced according to the steps described above, and a form for characterization demographic and clinical in mothers of children with neurological disorders awaiting care in a hospital reference in pediatric neurological care. After the pre-test were carried out the relevant changes, resulting in the final version of the study. Data from each translation step and cross-cultural adaptation (initial translation, synthesis of translations, back translation, and jugdes committee) were presented in tables and analyzed descriptively. Was used as statistical tests to analyze the process of translation and cultural adaptation the coefficient of Kappa to measure and evaluate the responses of judges, and the intraclass correlation coefficient (ICC) to verify the homogeneity of responses and assist in interpreting the proportion of variability of the same. The study was approved by the ethics committee in research via Brazil platform with the number 1320562. The results show that the main differences between inicials translations (1 translation and translation 2) referred to terms used in the health sector, having been translated more accurately by the translator that works in health sector. The backtranslation stage proved to be valid to guide the expert committee at the analysis in the next phase, helping to realize possible translations where could have happen some prejudice in the original sense of the sentence. The stage of review by a committee of judges, in which it evaluated all 31 items of the scale, as well as instructions and response options, using as criteria the semantic, idiomatic, experimental and conceptual, proved essential for analysis issues such as the translation of the term my child for my son to a faster understanding of the target population. It is believed that this study successfully performed the translation and adaptation of the scale, and is expected to contribute, after evaluation of the psychometric properties for the use of the scale in the Brazilian population. It is expected that further studies can contribute to the appreciation of the moment of contact with the mothers and fathers of children with neurological disorders, the pursuit of knowledge by health professionals on the social context that the family is inserted and social support, and targeting health practices by managers and professionals to assist in the reduction of uncertainty.